A Christmas Memory - Evans, Richard Paul (New York : Gallery Books, 2022)
The #1 New York Times bestselling King of Christmas Fiction is back this holiday season with another heartwarming and wintery tale of rediscovering faith and love. A coming-of-age holiday tale based on Richard Paul Evans's own childhood that shows us how hope and acceptance can be found in the most unexpected of places. -- From the publisher
1967. For young Richard it is a time of heartbreak and turmoil: his brother Mark is killed in Vietnam, his father loses his job and moves the family from California to Utah, and his parents decide to separate. When he's run down by bullies at his new school, Richard is rescued by Mr. Foster, an elderly neighbor. The man inspires Richard's love for books; Foster's dog, Gollum, becomes his companion. As a grim Christmas approaches, Richard learns for the first time what truly matters about the spirit of the season: that forgiveness can heal, and that love endures long after the pain of loss subsides. -- adapted from jacket
Text in English
BPL: David Winn Bishop and Isabel MacPherson Bishop Memorial Fund.
Keywords: Holidays -- Fiction; Families -- Fiction; Christmas stories; Death -- Fiction; Grief -- Fiction; Belief and doubt -- Fiction; Christmas fiction; Domestic fiction